1987
DOI: 10.3382/ps.0660258
|View full text |Cite
|
Sign up to set email alerts
|

Ahemeral Light-Dark Cycles and Egg Production Parameters of Ring-Necked Pheasants (Phasianus colchicus)

Abstract: The effects of two ahemeral light-dark (L:D) cycles on ring-necked pheasant egg production were investigated in this experiment. Three groups of 36 female and 12 male 10-month-old birds were exposed to control 24-hr (14L:10D), ahemeral 22-hr (14L:8D), or ahemeral 26-hr (14L:12D) L:D cycle. Average percent hen-day egg production (HDEP) was 63.8 for hens exposed to ahemeral 26-hr L:D cycle compared with 55.6% HDEP for the controls. Although this was not significant (P less than .05). It suggests a trend for phea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
3
1
0
Order By: Relevance
“…In this study there was no significant effect of storage time on egg weight. Egg weight values were similar to those reported by Woodard et al (1983), 30.6 g; Blake et al (1987), 31.9 to 34.4 g; Slaugh et al (1988), 31.00 to 32.3 g; Tserveni-Gousi and Yannakopoulos (1990), 30.49 g; Yannakopoulos (1992), 33.99 g; Çetin et al (1997) 33.36 g; Kırıkçı et al (2003b), 31.03 g; Günlü et al (2007), 30.22 to 32.19 g; and also Kırıkçı et al (2005), 31.89 and 31.16 g for brown and green eggs, respectively. However, the egg weights in the present study were higher than the values of 28.1 to 29.5 g reported by Woodard and Snyder (1978) and 25.79 g The differences between values with different superscript letters in the same column are significant (P < 0.05).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In this study there was no significant effect of storage time on egg weight. Egg weight values were similar to those reported by Woodard et al (1983), 30.6 g; Blake et al (1987), 31.9 to 34.4 g; Slaugh et al (1988), 31.00 to 32.3 g; Tserveni-Gousi and Yannakopoulos (1990), 30.49 g; Yannakopoulos (1992), 33.99 g; Çetin et al (1997) 33.36 g; Kırıkçı et al (2003b), 31.03 g; Günlü et al (2007), 30.22 to 32.19 g; and also Kırıkçı et al (2005), 31.89 and 31.16 g for brown and green eggs, respectively. However, the egg weights in the present study were higher than the values of 28.1 to 29.5 g reported by Woodard and Snyder (1978) and 25.79 g The differences between values with different superscript letters in the same column are significant (P < 0.05).…”
Section: Resultssupporting
confidence: 86%
“…Storage time did not significantly affect fertility ratio values. Fertility ratio determined in with the present study is similar to fertility ratios reported in previous studies (Woodard et al, 1983;Mashaly et al, 1983;Bates et al, 1987;Blake et al, 1987;Slaugh et al, 1988;Yannakopoulos, 1992;Çetin et al, 1997;Wadland, 2001, 2002;Kırıkçı et al, 2003b).…”
Section: Effect Of Different Egg Storage Timessupporting
confidence: 89%
See 1 more Smart Citation
“…The eggs were incubated at 37.7 C for 7 days. After this period, fertility was confirmed by ovoscopic analysis [3,37]. For this test only, pooled semen was used.…”
Section: Fertility Assessmentmentioning
confidence: 99%